INFORMATION ON POMEGRANATE PESTS (HEMIPTERA) WIDELY DISTRIBUTED IN FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
The article describes the distribution and biology of common pomegranate pests (Aphis (Aphis) punicae Passerini, 1863, Dialeurodes citri (Ashmead, 1885), Pseudococcus comstocki (Kuwana) Kuwana, Lepidosaphes ulmi (Linnaeus, 1758), Coccus pseudomagnoliarum (Kuwana, 1914) in the Fergana Valley.